High prevalence of CCDC103 p.His154Pro mutation causing primary ciliary dyskinesia disrupts protein oligomerisation and is associated with normal diagnostic investigations. Issue 2 (8th August 2017) - Shoemark, Amelia; Moya, Eduardo; Hirst, Robert A; Patel, Mitali P; Robson, Evelyn A; Hayward, Jane; Scully, Juliet; Fassad, Mahmoud R; Lamb, William; Schmidts, Miriam; Dixon, Mellisa; Patel-King, Ramila S; et al.
Abstract : Rationale: Primary ciliary dyskinesia is a genetically heterogeneous inherited condition characterised by progressive lung disease arising from abnormal cilia function. Approximately half of patients have situs inversus. The estimated prevalence of primary ciliary dyskinesia in the UK South Asian population is 1:2265. Early, accurate diagnosis is key to implementing appropriate management but clinical diagnostic tests can be equivocal. Objectives: To determine the importance of genetic screening for primary ciliary dyskinesia in a UK South Asian population with a typical clinical phenotype, where standard testing is inconclusive. Methods: Next-generation sequencing was used to screen 86 South Asian patients who had a clinical history consistent with primary ciliary dyskinesia. The effect of a CCDC103 p.His154Pro missense variant compared with other dynein arm-associated gene mutations on diagnostic/phenotypic variability was tested. CCDC103 p.His154Pro variant pathogenicity was assessed by oligomerisation assay. Results: Sixteen of 86 (19%) patients carried a homozygous CCDC103 p.His154Pro mutation which was found to disrupt protein oligomerisation. Variable diagnostic test results were obtained including normal nasal nitric oxide levels, normal ciliary beat pattern and frequency and a spectrum of partial and normal dynein arm retention. Fifteen (94%) patients or their sibling(s) had situs inversus suggesting CCDC103 p.His154Pro patients without situs inversus are missed. Conclusions: The CCDC103 p.His154Pro mutation is more prevalent than previously thought in the South Asian community and causes primary ciliary dyskinesia that can be difficult to diagnose using pathology-based clinical tests. Genetic testing is critical when there is a strong clinical phenotype with inconclusive standard diagnostic tests.